Principles and Practices of Winemaking - Boulton, Roger B., 1949-; Singleton, V. L. (Vernon L.); Bisson, Linda F.; Kunkee, R. E. (Ralph E.) (Springe, 1999)
This essential text and reference offers a complete guide to winemaking. The authors, all well-known experts in their field, concentrate on the process of wine production, stressing the chemistry, biochemistry, microbiology and underlying science of enology. They present in-depth discussion of every aspect of the wine production process, from the selection of grapes and preparation of the must and the juice, through aging, bottling and storage of finished wines. Novices and experienced winemakers alike will find this clearly written and expertly crafted book an indispensable source of practical instruction and information